Pengaruh Pembiayaan Bermasalah Dan Efisiensi Operasional Terhadap Profitabilitas Bank Syariah Periode 2013-2022 - Dela Setia; Muhammad Arif; Reni Ria Armayani Hasibuan (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
The focus of this study is to determine the effect of variable X1 financing problems and variable X2 operational efficiency on variable Y profitability of PT Bank Muamalat Indonesia within a predetermined time span, namely the 2013-2022 period. Quantitative research methods with associative approaches and documentation data collection techniques are used in this study. Secondary data sources come from all financial ratio reports of PT Bank Muamalat Indonesia which are also the population and 40 financial reports in quarterly form from the 2013-2022 period as a sample. Eviews 12.0 was used to process data with the R2 test, T test, F test and the classical assumption test considered across multiple linear regression. According to the results of simultaneous hypothesis testing. Based on the analysis of the NPF and BOPO variables, it was found that Fcount was 808.5030 and Ftable was 3.252, which means Fcount > Ftable, so the results of this test indicated that both NPF and BOPO simultaneously had a significant effect on ROA. Through the t test the NPF variable has a tcount value of 2.379788 and a probability of 0.0226 when compared to ttable = 2.026, meaning that the value of tcount > ttable corresponds to the results of the t test. Then H0 is rejected and Ha is accepted. The significance value of BOPO is 0.0000, which is less than 0.05, thus indicating the result that BOPO has a significant effect on ROA. thus giving an illustration that H0 is rejected and Ha is accepted.